Analysis of Career Planning Level of High School Students: The Impact of Career Counseling in Schools - Sapitri, Sumiati; Syafiq, Mohamad (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Career planning is an important aspect of students' personal and professional development. Understanding the current level of students' career planning can help educators and counselors provide targeted guidance. Objective: The purpose of this study was to determine the profile of students' career planning levels at SMA Negeri 11 Bandung. Method: The research used a quantitative approach and was conducted at SMA Negeri 11 Bandung in 2022. The sample consisted of 90 students. Data collection techniques included questionnaires, observation, and documentation studies. Result: The findings indicate that (1) the majority of the sample were female students; (2) third-grade students demonstrated a higher level of career planning compared to first- and second-grade students; (3) the most common level of career planning among students was in the 'Moderate' category. Conclusion: The study concluded that the majority of students at SMA Negeri 11 Bandung have a 'Moderate' level of career planning. Contribution: These results can serve as a consideration and an alternative strategy for developing effective career planning programs for students.